Safety and Efficacy of Rapamycin-Eluting Vertebral Stents in Patients With Symptomatic Extracranial Vertebral Artery Stenosis - Ma, Gaoting; Song, Ligang; Ma, Ning; Raynald,; Shuai, Jie; Wu, Wei; Wan, Jieqing; Zhao, Zhenwei; Li, Guangjian; Yin, Sen; Ding, Shenghao; Li, Jiang; et al. (Frontiers in Neurology, 2021)
Background and Purpose: Drug-eluting stents generally have superior performance to bare metal stents in the treatment of vertebral artery stenosis (VAS). This prospective, multicenter, and single-arm clinical trial was initiated to assess in-stent restenosis (ISR) and midterm outcome after rapamycin-eluting stent placement in patients with symptomatic extracranial VAS. Methods: The subjects underwent angiographic follow-up at 6 months and final clinical follow-up at 12 months. The primary efficacy endpoint was ISR at 6 months. Secondary endpoints included technical success, target lesion-related transient ischemic attack (TIA), stroke, or death, and all-cause TIA, stroke, or death during the 12-month follow-up period. Results: A total of 104 stents were implanted in the 101 patients and 83 patients (82.2%) completed angiographic follow-up at 6 months. The technical success rate was 86.1% (87/101); mean in-stent stenosis rate was 25.1 ± 17.1% and ISR rate was 5.9% (95% CI: 0.8–10.9%). All the patients with ISR were completely asymptomatic and no stent fractures were observed during angiographic follow-up. At the 12-month clinical follow-up, target lesion-related TIA, stroke, or death had occurred in two (2.0%) patients and all-cause TIA, stroke, or death had occurred in six (6.1%) patients. Conclusion: The placement of rapamycin-eluting stents in patients with symptomatic extracranial VAS yields favorable ISR results and showed a trend of favorable safety outcomes including low rates of perioperative complications and late stroke. However, further study is needed to establish the long-term clinical benefits of this stent in the treatment of VA disease.